Role of smartphone devices in motivation to study in the Covid-19 Pandemic - S., Herlambang; Wahyudiyono, Wahyudiyono; A., Subiyantoro; Jumintono, Jumintono; L., Madu; R., Hartati (TMU, 2021)
Aims The sudden COVID-19 pandemic experienced globally has caused many schools and institutions of higher learning to resort to fully online teaching and learning throughout the world. Since online teaching is essentially a student-centered learning approach, students’ motivational level plays an important role in making teaching protocols effective. This study aimed to know the level of motivation to study using a smartphone in the COVID-19 pandemic. Instrument & Methods This descriptive study was carried out in 2020 on 75 Indonesian Academy of Administrative Management College students who have smartphones. These students were selected by random sampling method. Data were collected using a researchermade questionnaire and analyzed by SPSS 17 software using Pearson correlation coefficient and simple linear regression test. Findings There was a positive and significant correlation between the mean score of smartphone usage and the mean score of study motivation (r=0.84; p=0.0001). The effect of smartphone uses on the study motivation in the Covid-19 pandemic was 61.7% (R2=0.617). Conclusion With the increasing use of smartphones, the motivation to learn during pandemic COVID-19 also increased.